Management of HIV-hepatitis B co-infection - Marc Mendelson (AOSIS, 2011)
HIV-hepatitis B virus (HBV) co-infected patients are at risk of increased morbidity and mortality. Early recognition of dual infection is a critical factor in directing appropriate therapy, and HBV screening should therefore be undertaken at the time of HIV diagnosis. Vaccination against HBV should be considered for all HIV patients who are not yet infected with HBV. Antiretroviral therapy containing two antiretrovirals active against HBV should be started if the patient either has symptomatic liver disease or is asymptomatic with a CD4 count of